2009
DOI: 10.3399/bjgp09x420941
|View full text |Cite
|
Sign up to set email alerts
|

Telephone consulting in primary care: a triangulated qualitative study of patients and providers

Abstract: Internationally, there is increasing use of telephone consultations, particularly for triaging requests for acute care. However, little is known about how this mode of consulting differs from face-to-face encounters. AimTo understand patient and healthcare-staff perspectives on how telephone consulting differs from face-to-face consulting in terms of content, quality, and safety, and how it can be most appropriately incorporated into routine health care. Design of studyFocus groups triangulated by a national q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
2
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 16 publications
5
123
2
9
Order By: Relevance
“…30 However, the small number of examples in the present data of doctors and patients successfully consulting at length by telephone about complex continuing problems, support the researchers' previous finding that it is a medium that could be used more frequently for the care of patients with long-term conditions. 31 The doctors in the study sample who are consulting by telephone do not elicit additional concerns from patients nor, with a few notable exceptions, do the patients introduce additional problems by making use of recognised communicative strategies such as mention of more than one concern at the beginning of consultations. 32 This supports the evidence from the recent triangulated focus group study which shows that both doctors and patients consulting by telephone expect to pursue limited agendas.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…30 However, the small number of examples in the present data of doctors and patients successfully consulting at length by telephone about complex continuing problems, support the researchers' previous finding that it is a medium that could be used more frequently for the care of patients with long-term conditions. 31 The doctors in the study sample who are consulting by telephone do not elicit additional concerns from patients nor, with a few notable exceptions, do the patients introduce additional problems by making use of recognised communicative strategies such as mention of more than one concern at the beginning of consultations. 32 This supports the evidence from the recent triangulated focus group study which shows that both doctors and patients consulting by telephone expect to pursue limited agendas.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Detailed analyses of the clinician-patient interaction using conversation analysis have found that, compared with traditional face-to-face consulting, telephone consultations have a more linear format and tend to focus on a narrow range of preplanned themes, with fewer opportunities for the patient to raise ad hoc issues. 34,35 One study combined telephone consulting with video consultation to support patients receiving palliative care and reported that the combination offered both practical support and reassurance. 45 …”
Section: Telephonementioning
confidence: 99%
“…Telephone contact is used variably for assessment and triage of acute problems; [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] general practice consultations; [34][35][36][37][38][39][40] to offer health education; 41,42 and to offer support for those with chronic illness 43,44 or those in need of palliative care. 45 The literature on telephone consultations consists largely of small and heterogeneous primary studies, most of which had practical challenges or methodological flaws.…”
Section: Telephonementioning
confidence: 99%
“…(Katz et al, 2008) In terms of safety, more than 70% of clinicians and 60% of patients were concerned that clinicians would be more likely to make a wrong/inaccurate diagnosis in telephone consultation compared to face-to-face consultations. (McKinstry et al, 2009) Challenges with telephone consultations include the lack of nonverbal clues, no direct observations and examinations, lack of active listening as the physician might be engaged in his own activities at time of call and talking to family members. Mobile phone cameras and audio recording can have the potential to compensate for the lack of observations.…”
Section: Safety Concernsmentioning
confidence: 99%